A retrospective analysis of electrocardiographic abnormalities found in black South African patients with diabetes attending a regional hospital in KwaZulu-Natal. Issue 3 (27th September 2017) - Pillay, S; Hift, R; Aldous, C
Abstract : Objectives: Diabetes mellitus increases the risk of coronary heart disease and myocardial infarction (MI). Silent MI occurs with greater frequency in patients with diabetes with or without autonomic neuropathy and carries a similar prognosis to overt MI. Regular electrocardiographic (ECG) assessment is integral in the chronic management of patients with diabetes. Limited data exist on the spectrum of ECG abnormalities of black South African patients with diabetes. The primary aim of this study was a description of ECG abnormalities found and the secondary aim was the determination of factors associated with left ventricular hypertrophy (LVH) and MI. Setting and participants: The study was carried out at a regional hospital diabetes clinic in Pietermaritzburg, KwaZulu-Natal. The initial ECGs performed on patients from October 1, 2012 to September 30, 2014 were analysed. The first ECGs of 637 black South African patients with diabetes were studied, representing 80.1% of all eligible patients. Results: The major ECG abnormalities detected were those suggestive of LVH (36.0%), MI (21.7%), conduction defects (17.7%), T-wave inversion (14.1%) and ventricular ectopics (6.8%). Most infarctions were silent (89.8%), and affected the inferior territory significantly more than anterior, lateral and antero-lateral territories (52.9% vs. 33.3% vs. 9.4% vs. 1. 5%, respectively). A substantial percentage of patients with MI failed to achieve target HbA1c and triglyceride levels and waist-to-height-ratios. Diet, exercise and self-monitoring of glucose were all associated with positive effects on both MI and LVH. A greater percentage of patients with LVH had evidence of MI versus those without hypertrophy (28.4% vs. 19.4%). Conclusion: This study demonstrates a high prevalence of undiagnosed MI within this cohort of South African patients with diabetes. Patients with LVH were more prone to infarction. Poor glycaemic and triglyceride control and obesity were associated with infarction. Improving glycaemic and lipid control together with lifestyle modification may help prevent macrovascular cardiac complications.